2012
DOI: 10.4012/dmj.2012-098
|View full text |Cite
|
Sign up to set email alerts
|

Corrosive effect of disinfection solution containing hydroxyl radicals generated by photolysis of H2O2 on dental metals

Abstract: The purpose of the present study was to evaluate the corrosive effect of disinfection solution containing hydroxyl radicals generated by photolysis of H 2 O 2 on dental metals. Static immersion test was performed on four different dental metals: Ti, Type 316L stainless steel, Ag-Pd-Cu-Au alloy, and Co-Cr alloy. Metal specimens were immersed in 1 M H 2 O 2 (=3.4%) with or without light-emitting diode (LED) light irradiation (wavelength: 400 nm) for 1 week, and then the amounts of released ions were analyzed. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
(29 reference statements)
0
9
0
1
Order By: Relevance
“…Their results suggest that discoloration in titanium alloys immersed in hydrogen peroxidecontaining acidulated solutions is caused by an increase in the thickness of this oxide film, whereas discoloration of Ti-Ni is caused by corrosion. Nakamura et al 33 evaluated the corrosive effect of disinfection solution containing hydroxyl radicals generated by photolysis of H 2 O 2 on dental metals (Ti, Type 316L stainless steel, Ag-Pd-Cu-Au alloy and Co-Cr alloy) and observed that hydrogen peroxide can be applied to denture cleaning device without problematic metal corrosion unless the dentures contain Ti components.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggest that discoloration in titanium alloys immersed in hydrogen peroxidecontaining acidulated solutions is caused by an increase in the thickness of this oxide film, whereas discoloration of Ti-Ni is caused by corrosion. Nakamura et al 33 evaluated the corrosive effect of disinfection solution containing hydroxyl radicals generated by photolysis of H 2 O 2 on dental metals (Ti, Type 316L stainless steel, Ag-Pd-Cu-Au alloy and Co-Cr alloy) and observed that hydrogen peroxide can be applied to denture cleaning device without problematic metal corrosion unless the dentures contain Ti components.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the amounts of hydroxyl radicals generated and remaining H2O2 after the immersion test, two additional experiments as described in our previous studies 11,23) after LED irradiation The concentration of H 2O2 was expected to decrease with Fig. 2 Flexural strengths of acrylic denture base resin specimens after the immersion test expressed in mean value with standard deviation (n=5).…”
Section: Quantification Of Hydroxyl Radical and H 2o2mentioning
confidence: 99%
“…In the present study, photolysis of 1 M H 2O2 was carried out using an experimental LED irradiation device as described in our previous study 11) . Each chamber of the experimental device was equipped with two LED light sources, which emitted light with a wavelength of 400 nm (NHH105UV, Lustrous Technology, Shiji, Taipei, Taiwan) 21) .…”
Section: Experimental Led Irradiation Devicementioning
confidence: 99%
See 2 more Smart Citations